EXPERIENCE DE LA MACHINE A VOTER LORS DU SCRUTINS DU 30 DECEMBRE 2018 EN REPUBLIQUE DEMOCRATIQUE DU CONGO : ENJEUX ET PERSPECTIVES. - NZAMBE, Jean-Paul LETUNITA; Louis NZOSHALE NGOSHALE; Aimé BAVI GONDJI; Prince LONU LOTSIMA; Angel NAMAWA MAGIDRIKO (IJRDO - Journal of Social Science and Humanities Research, 2020)
The desire to democratise Africa is a good wind that requires the support and backing of all African leaders. We know that democracy is a process that has preconditions that must be respected. Elections are one of the important pillars that support democracy in all its essence. Digital technology, adopted to ensure the credibility of electoral results, has come to confirm its importance in certain measures beyond all doubt. The voting machine in the process of democratisation of Africa constitutes one of the important tools by the fact that this technology does not offer the possibility of fraud or electronic cheating, but if there are disputes or falsification of results is that the problem exists beyond the machine, it is at the level of processing, transmission and publication of results. This digital technology has no compromise on the process of democratisation of the African continent. It would be more than question and desirable for a perspective approach to constitute a commission whose mission would be to watch and monitor the processing, transmission and publication of electoral results in Africa.